QUANTITATIVE ASSESSMENT OF EARNINGS MANIPULATION AND FUNDAMENTAL STRENGTH AT PT GARUDA INDONESIA (PERSERO) TBK USING THE BENEISH M-SCORE AND PIOTROSKI F-SCORE (2019–2021; 2018 BASELINE) - Andi Muhammad Firzan Surianto; Erman Arif Sumirat (Journal of Economic, Bussines and Accounting (COSTING), 2026)
This thesis examines PT Garuda Indonesia (Persero) Tbk over 2018–2021 to provide a clear, rules-based view of its condition after the 2018 incident. The study asks two main questions: did manipulation signals in the financial statements decline after 2018, and did the company’s fundamental strength improve in the same years? Using 2018 as a baseline, the research expects post-incident years (2019–2021) to show an M-Score that is more negative and an F-Score that is higher. Reading both indicators together allows a simple judgement about Garuda’s post-incident trajectory that is useful for investors, creditors, regulators, and management. Methodologically, the study is quantitative, single-firm, and longitudinal. It uses audited annual financial statements (2018–2021) and harmonised definitions across years. The analysis computes the Beneish M-Score from eight indices to read manipulation risk and the Piotroski F-Score from nine signals to measure fundamentals. Each year is classified with standard rules, then compared with 2018 to obtain ΔM (more negative?) and ΔF (higher?). Results are read together to identify convergence (M↓ & F↑) or divergence, providing a concise, replicable picture of Garuda Indonesia after 2018.